A peg-in-hole controller for cable-driven serial robots with compliant wrist based on cable tensions and joint positions. Issue 1 (21st December 2021) - Lou, Ya'nan; Quan, Pengkun; Lin, Haoyu; Liang, Zhuo; Wei, Dongbo; Di, Shichun
Abstract : Purpose: This purpose of this paper is to design a peg-in-hole controller for a cable-driven serial robot with compliant wrist (CDSR-CW) using cable tensions and joint positions. The peg is connected to the robot link through a CW. It is required that the controller does not rely on any external sensors such as 6-axis wrist force/torque (F/T) sensor, and only the compliance matrix's estimated value of the CW is known. Design/methodology/approach: First, the peg-in-hole assembly system based on a CDSR-CW is analyzed. Second, a characterization algorithm using micro cable tensions and joint positions to express the elastic F/T at the CW is established. Next, under the premise of only knowing the compliance matrix's estimate, a peg-in-hole controller based on force/position hybrid control is proposed. Findings: The experiment results show that the plug contact F/T can be tracked well. This verifies the validity and correctness of the characterization algorithm and peg-in-hole controller for CDSR-CWs in this paper. Originality/value: First, to the authors' knowledge, there is no relevant work about the peg-in-hole assembly task using a CDSR-CW. Besides, the proposed characterization algorithm for the elastic F/T makes the peg-in-hole controller get rid of the dependence on the F/T sensor, which expands the application scenarios of the peg-in-hole controller. Finally, the controller does not require an accurate compliance matrix, which also increases its applicability.